Respuesta :
the answer
f(x) = 0.7(6)x = f(x) = 0.7(6)^x, and g(x) = 0.7(6)–x= g(x) = 0.7(6)^-x=1/0.7(6)^x
so
g(x) =1/0.7(6)^x=1 /f(x)
the relationship between f and g are g(x) =1 /f(x) or g(x) . f(x) = 1
f(x) = 0.7(6)x = f(x) = 0.7(6)^x, and g(x) = 0.7(6)–x= g(x) = 0.7(6)^-x=1/0.7(6)^x
so
g(x) =1/0.7(6)^x=1 /f(x)
the relationship between f and g are g(x) =1 /f(x) or g(x) . f(x) = 1
Answer:
the answer
f(x) = 0.7(6)x = f(x) = 0.7(6)^x, and g(x) = 0.7(6)–x= g(x) = 0.7(6)^-x=1/0.7(6)^x
so
g(x) =1/0.7(6)^x=1 /f(x)
the relationship between f and g are g(x) =1 /f(x) or g(x) . f(x) = 1
Step-by-step explanation: